2011
DOI: 10.1042/cbi20100719
|View full text |Cite
|
Sign up to set email alerts
|

Putative Arabidopsis homologues of metazoan coiled‐coil cytoskeletal proteins

Abstract: The Arabidopsis thaliana genome encodes about 386 proteins with coiled-coil domains of at least 50 amino acids in length. In mammalian systems, many coiled-coil proteins are part of various cytoskeletal networks including intermediate filament protein, actin-binding proteins and MAP (microtubule-associated proteins). Immunological evidence suggests that some of these cytoskeletal proteins, such as lamins, keratins and tropomyosins, may be conserved in Arabidopsis. However, coiled-coil proteins are of low compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 72 publications
2
47
0
Order By: Relevance
“…Recent analysis based on secondary structure for analogues of Arabidopsis coiled-coil proteins indicates that CRWN proteins are candidates for paramyosin homologues [11]. Paramyosin is a structural protein found in invertebrate muscles, where it forms the core of thick filaments and bundles with myosin motors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent analysis based on secondary structure for analogues of Arabidopsis coiled-coil proteins indicates that CRWN proteins are candidates for paramyosin homologues [11]. Paramyosin is a structural protein found in invertebrate muscles, where it forms the core of thick filaments and bundles with myosin motors.…”
Section: Discussionmentioning
confidence: 99%
“…Although NMCP1 and related proteins are plant-specific and share no significant amino acid similarity to lamins, their tripartite structure with an extensive central coiled-coil domain and their localization at the nuclear periphery suggest that NMCP1-related plant proteins might be functional analogs of this core component of the animal nuclear lamina [9,10]. More recent computational analysis [11], however, has suggested that the NMCP class of plant proteins shares more structural similarities to myosins or paramyosins than to lamins.…”
Section: Introductionmentioning
confidence: 99%
“…In metazoans, coiled-coil proteins group as various cytoskeletal networks comprising intermediate filament proteins, actin-binding proteins, and microtubule-associated proteins (Burkhard et al , 2001; Korolev et al , 2005). Albeit several proteins closely related to the intermediate filament protein were identified in silico (Gardiner et al , 2011), knowledge of plant coiled-coil proteins is limited. The current work found that overproduced AtTPX2 accumulated in interphase nuclei and observed TPX2-dependent fibrillar arrays interconnecting nuclei with the nuclear periphery.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent paper suggested that AtMAP70 may be related to animal intermediate filaments. 19 In plants, MAP70s are organized into a small multigenic family ranging from two isoforms in Selaginella sp. to ten in Glycine max (Fig.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%